Procedural Pain Assessment in Infants Without Analgosedation: Comparison of Newborn Infant Parasympathetic Evaluation and Skin Conductance Activity - A Pilot Study - Walas, Wojciech; Halaba, Zenon P.; Szczapa, Tomasz; Latka-Grot, Julita; Maroszyńska, Iwona; Malinowska, Ewelina; Rutkowska, Magdalena; Kubiaczyk, Agata; Wrońska, Monika; Skrzypek, Michał; De Jonckheere, Julien; Jean-Noel, Mickael; et al. (Frontiers in Pediatrics, 2022)
Objective: New technologies to measure pain responses, such as heart rate variability and skin conductance hold promise in the development of tools that can be reliable and quantifiable of detecting pain. The main objective of this study was to assess the capability of two monitors i.e. Newborn Infant Parasympathetic Evaluation (NIPE) and Skin Conductance Algesimeter for detecting procedural pain in non-anaesthetized infants. Materials and methods: Thirty-three non-anaesthetised infants were enrolled to the study. To detect pain caused by heel stick, NIPE, and Skin Conductance monitors and behavioural pain scales were used. Three minutes before and just after heel stick, pain was evaluated by behavioural scales, and simultaneously over the whole period by NIPE and SCA. Results: A statistically significant decrease of NIPE Index and an increase of SCA values were found after the HS procedure. Conclusions: Both NIPE and SCA are useful for detection of procedural pain and may constitute an important tool for better handling of pain among patients treated in NICUs.